COMPARISON OF 18 F-FDG AND 18 F-PSMA-1007 PET/CT IN ADVANCED LOCOREGIONAL SQUAMOUS CELL CARCINOMA OF HEAD AND NECK: PRELIMINARY RESULTS - Hadila Da Silva Veras Sousa; Kaique Moraes do Amaral; Najua Abou Arab; Simone Kuba; Lígia Traldi Macedo; Bárbara Juarez Amorim; Celso Dario Ramos; Carmen Silvia Passos Lima (Hematology, Transfusion and Cell Therapy, 2024)
Introduction/Justification: Head and neck squamous cell carcinoma (HNSCC) is a health problem worldwide. Most patients with HNSCC have locally advanced disease, and progression or relapse of the tumor after treatment are common events. Imaging exams to assess the existence and/or extent of the tumor play a crucial role in managing these patients. 18 F-FDG and 18 F-PSMA-1007 are markers of glycolytic activity and neo angiogenesis, respectively. The PET/CT images performed with 18 F-FDG (FDG PET/CT) have unequivocal contribution in HNSCC, but the importance of the images with 18 F-PSMA- 1007 (PSMA PET/CT) in tumor is still unclear. Objectives: The aim of this study was to describe the findings of FDG PET/CT and PSMA PET/CT in patients with advanced locoregional HNSCC at diagnosis or relapse with the purpose of verifying whether any of these exams is more suitable for detecting the tumor. Materials and Methods: Patients with advanced locoregional HNSCC at diagnosis or relapse of HNSCC were enrolled in study. Patients who underwent surgical resection of the tumor or treatment with radio chemotherapy in the last six months were excluded from the study. All patients were submitted to FDG PET/CT and PSMA PET/CT with a 24-hour interval between exams. Two nuclear medicine physicians and one radiologist analyzed the images. Comparisons between groups were analyzed by t-test, and differences were significant when p-values were < 0.05. Results: Five patients (three patients at diagnosis and one relapsed patient) were analyzed by both PET/CT images. The median age of patients was 60 years old (variation: 52-75), four were males and 1 was female. Most patients were smokers/ex- smokers and/or drinkers/ex-drinkers, had good performance status (ECOG 0), and presented tumors at stage IV. The primary tumor was localized in oropharynx/larynx (with lymph node isease), and relapses were seen mainly in lungs, liver, and bone. The HNSCC lesions were typically characterized by FDG uptake, but most lesions also exhibited varying degrees of PSMA uptake. In primary tumors and lymph node disease, mean ± SD and median (min-max) values of SUV found with FDG PET/CT scan at 1 hour were 21.1 ± 7.6 and 21.0 (14.0-33.1) and 9.0 ± 6.1 and 7.2 (2.7-18.8), respectively. For PSMA PET/CT scan, mean ± SD and median (min-max) values of SUV at 1 hour in primary tumors and lymph nodal disease were 4.0 ± 1.0 and 3.7 (2.9-5.3) and 9.0 ± 6.1 and 7.2 (2.7-18.8), respectively. The values of FDG uptake were higher than values of PSMA uptake in both primary tumors (p = 0.001) and lymph nodes (p = 0.02). Conclusion: HNSCC lesions were better detected by PET/CT images with 18F-FDG than with 18 F-PSMA-1007. The uptake of both markers in most tumors indicates that glycolytic activity and neoangiogenesis occur in HNSCC, enabling a more personalized approach in patient management. Nevertheless, the current study's sample size was small to draw conclusive results. Acknowledgements: The study was supported by Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), Fundação de Apoio ao Ensino e à Pesquisa do Estado de São Paulo (Cancer Theranostics Innovation Center, CancerThera, CEPID FAPESP #2021/10265-8), nd International Atomic Energy Agency (IAEA) technical cooperation projects for development of Latin American Countries (IAEA/TCLAC: EX-BRA6033-2401375).